Phyto- and zooplankton paleofluxes during the deposition of sapropel S1 (eastern Mediterranean): Biogenic carbonate preservation and paleoecological implications - M. S. PRINCIPATO; D. CRUDELI; P. ZIVERI; C. P. SLOMP; C. CORSELLI; G. J. DE LANGE; E. ERBA (Palaeogeography, Palaeoclimatology, Palaeoecology, 2006)
The relative and absolute abundances and accumulation rates of forarninifera and calcareous nannofossils were quantified in a box core containing sapropel S I from the Florence Rise area (SE of Cyprus; 2302 m water depth). The main objective of this study was to reconstruct in detail variations in paleoecological conditions of water masses during the deposition of this sapropel. In particular, we qualitatively evaluated the importance of carbonate dissolution on planktonic assemblages to better interpret the abundance profiles obtained from the two investigated taxa. Selective carbonate corrosion in the core is shown by (1) the decrease in shell mass weight of selected species of planktonic foraminifera, (2) the decrease in accumulation rate of dissolution-susceptible holococcoliths and coccolith species, and (3) the absence of pteropods. However, the presence of other relatively dissolution-susceptible coccolith species throughout all of the S I interval suggests moderate dissolution. Florisphaera profunda shows a marked increase in paleofluxes within the sapropel coupled with a decrease in the accumulation rate of the upper-middle photic zone coccoliths, suggesting an ecological depth-separation of the water column, probably characterised by higher nutrient availability at depth and nutrient-depleted surface waters between similar to 10 and 6.5 kyr BR In the same interval Turborotalita quinqueloba and Globigerina bulloides, two formaniniferal species frequently occurring during periods of high fertility, increase in relative abundance. The maximum increase in relative abundance of Globigerinoides ruber (var. alba and rosea) marks the climatic optimum phase and the maximum stratification in surface water that occurred at the beginning of sapropel S1 deposition when the bottom waters were anoxic. An important change in foraminiferal assemblages occurs at similar to 8 kyr BP and corresponds with a negative shift in CaCO3, Ba and C-org contents. This short interval marks the establishment of relatively less anoxic ...